2012
DOI: 10.1016/j.fm.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

pilF polymorphism-based real-time PCR to distinguish Vibrio vulnificus strains of human health relevance

Abstract: a b s t r a c tThe Gram-negative bacterium Vibrio vulnificus is a common inhabitant of estuarine environments. Globally, V. vulnificus is a significant foodborne pathogen capable of causing necrotizing wound infections and primary septicemia, and is a leading cause of seafood-related mortality. Unfortunately, molecular methods for the detection and enumeration of pathogenic V. vulnificus are hampered by the genetically diverse nature of this pathogen, the range of different biotypes capable of infecting humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Furthermore, the genetic arrangement of the putative hemolysin and TRAP transporter genes (HEMOTRAP), similar to the published genomes (49), was also present exclusively in cluster IIA. All cluster II strains possessed pilF type C, which has previously been correlated with pathogenicity (1,28) and was only rarely found in cluster I BT1 strains. In contrast to the study of Roig et al (28), in which nearly all clinical isolates possessed the pilF type C allele, more than half of the clinical strains in our strain collection possessed pilF type E. Altogether, our data on the distribution of type C and E alleles of the pilF, 16S rRNA, and vcg genes among environmental and clinical isolates from the Baltic Sea region support the opinion of Thiaville et al that E-type strains can be pathogenic and should not be classified as avirulent per se (31).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Furthermore, the genetic arrangement of the putative hemolysin and TRAP transporter genes (HEMOTRAP), similar to the published genomes (49), was also present exclusively in cluster IIA. All cluster II strains possessed pilF type C, which has previously been correlated with pathogenicity (1,28) and was only rarely found in cluster I BT1 strains. In contrast to the study of Roig et al (28), in which nearly all clinical isolates possessed the pilF type C allele, more than half of the clinical strains in our strain collection possessed pilF type E. Altogether, our data on the distribution of type C and E alleles of the pilF, 16S rRNA, and vcg genes among environmental and clinical isolates from the Baltic Sea region support the opinion of Thiaville et al that E-type strains can be pathogenic and should not be classified as avirulent per se (31).…”
Section: Discussionmentioning
confidence: 66%
“…It can cause serious wound infections with lethal outcome and is also responsible for cases of death caused by consumption of contaminated seafood. In the United States, particularly oysters contaminated with V. vulnificus have been reported to be responsible for deadly infections (1)(2)(3). The severity of disease is strongly influenced by the health condition of exposed individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Roig et al (64) demonstrated that pilF is a good genetic marker for human virulence potential in this species because it is correlated to human serum resistance. The same authors developed a multiplex PCR methodology to identify the strains potentially dangerous for public health and, later, Baker-Austin et al (65) developed a real-time PCR assay for their detection from oysters. PilF is a protein required for pilus type IV assembly, whose mutation in other bacterial pathogens is involved in attenuated virulence for mice (66).…”
Section: Phylogenymentioning
confidence: 99%
“…This homogeneity is not observed when trying to assess the pathogenic potential of the bacterium, where several targets have been proposed, such as the rtxA, vcgC/E (virulence-correlated gene clinical/environmental), and 16S rRNA type A (environmental) and type B (clinical) (Drake, Whitney, Levine, DePaola, & Jaykus, 2010; Rosche, Binder, & Oliver, 2010;Rosche, Yano, & Oliver, 2005). Recently, a polimorfism in the pilF gene has been described as a good marker of the pathogenic potential of V. vulnificus (Baker-Austin et al, 2012;Fajardo et al, 2014;GarridoMaestu, Chapela, Román, Vieites, & Cabado, 2014;Roig, Sanjuan, Llorens, & Amaro, 2010).…”
Section: Vibrio Vulnificusmentioning
confidence: 99%